Synthesis and Antibacterial Activities of Some 2H-Chromen-2-one Derivatives - Vaso, Kozeta; Behrami, Aziz; Govori, Sevdije; Vehapi, Idriz (Asian Journal of Chemistry, 2011)
This work reports the syntheses of some new 2H-chromen-2-one derivatives and their antibacterial activity. 4-(Naphthalen-1-ylamino)-2-oxo-2H-chromen-3-carbaldehyde (a1), N-(3-formyl-2-oxo- 2H-chromen-4-yl)-N-naphthalen-1-yl-benzamide (a2), N-(7-butylamino-3-formyl-2-oxo-2Hchromen- 4-yl)-N-naphtalen-1-yl-benzamide (a3) have been synthesized and characterized by IR spectra, 1H NMR spectra and elemental analyses. The purified synthesized compound a3 at concentrations 2, 3 and 5 mg/mL was subjected to test the antibacterial activity against three bacterial cultures; Staphylococcus aureus, Escherichia coli and Bacillus cereus. The antibacterial activity of synthesized compounds were compared with antibacterial activity of the standard antibiotics cephalexine and streptomycine. The compound shows different bacteriostatic and bactericidal activity.